Large electric field-induced strain and piezoelectric responses of lead-free Bi0.5(Na0.80K0.20)0.5TiO3-Ba(Ti0.90Sn0.10)O3 ceramics near morphotropic phase boundary - Pharatree Jaita (2018)
© 2015, The Korean Institute of Metals and Materials and Springer Science+Business Media Dordrecht. Lead-free piezoelectric ceramics with compositions belonging to family of compositions (1−x)Bi < inf > 0.5 < /inf > (Na < inf > 0.80 < /inf > K < inf > 0.20 < /inf > ) < inf > 0.5 < /inf > TiO < inf > 3 < /inf > -xBa(Ti < inf > 0.90 < /inf > Sn < inf > 0.10 < /inf > )O < inf > 3 < /inf > or (1−x) BNKT-xBTS (when x = 0.05 − 0.15 mol fraction) near the morphotropic phase boundary (MPB) were fabricated by a conventional mixed oxide method. Sintered samples had relative densities greater than 98% of their theoretical values. X-ray diffraction data revealed that the MPB region consisted of coexisting rhombohedral and tetragonal phases in the BNKT-BTS system was identified over the entire compositional range. A large electric field-induced strain (S < inf > max < /inf > ) of 0.36% and a normalized strain coefficient (d* < inf > 33 < /inf > ) of 649 pm/V were observed in the BNKT-0.05BTS sample. The sample close to the MPB composition (BNKT-0.11BTS) exhibited the maximum dielectric constant (ε < inf > r < /inf > = 1770), temperature of maximum permittivity (T < inf > m < /inf > = 333C°) and low-field piezoelectric coefficient (d < inf > 33 < /inf > = 227 pC/N), along with reasonable ferroelectric properties (P < inf > r < /inf > = 20.6 mC/cm < sup > 2 < /sup > , R < inf > sq < /inf > = 0.88) and strain properties (d* < inf > 33 < /inf > = 445 pm/V and S < inf > max < /inf > = 0.24%). [Figure not available: see fulltext.]